2020
DOI: 10.1002/jts.22497
|View full text |Cite
|
Sign up to set email alerts
|

Positive Emotion Dysregulation Among Community Individuals: The Role of Trauma Exposure and Posttraumatic Stress Disorder

Abstract: Existing literature has provided support for an association between posttraumatic stress disorder (PTSD) and emotion dysregulation. However, few studies have examined the relation between PTSD and emotion dysregulation that stems from positive emotions. Moreover, the role of trauma exposure, per se, on positive emotion dysregulation is unknown. Addressing these limitations, the current study compared levels of positive emotion dysregulation among (a) individuals without trauma exposure, (b) trauma-exposed indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 60 publications
1
27
0
Order By: Relevance
“…Important variables to consider in this regard are positive emotion dysregulation (i.e., nonacceptance of positive emotions, difficulties engaging in goal‐directed behaviors when experiencing positive emotions, and difficulties controlling impulsive behaviors when experiencing positive emotions) and fear of positive emotions. Notably, such positive emotion constructs are associated with both PTSD severity (Weiss, Contractor, Forkus, Goncharenko, & Raudales, in press; Weiss, Dixon‐Gordon, Peasant, & Sullivan, 2018; Weiss, Nelson, Contractor, & Sullivan, 2020) as well as with memory retrieval (Josephson,1996; Quoidbach, Mikolajczak, & Gross, 2015; Rusting & DeHart, 2000). Thus, the current study examined if the PTSD‐positive memory relationship is influenced and altered by positive emotion dysregulation and fear of positive emotions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Important variables to consider in this regard are positive emotion dysregulation (i.e., nonacceptance of positive emotions, difficulties engaging in goal‐directed behaviors when experiencing positive emotions, and difficulties controlling impulsive behaviors when experiencing positive emotions) and fear of positive emotions. Notably, such positive emotion constructs are associated with both PTSD severity (Weiss, Contractor, Forkus, Goncharenko, & Raudales, in press; Weiss, Dixon‐Gordon, Peasant, & Sullivan, 2018; Weiss, Nelson, Contractor, & Sullivan, 2020) as well as with memory retrieval (Josephson,1996; Quoidbach, Mikolajczak, & Gross, 2015; Rusting & DeHart, 2000). Thus, the current study examined if the PTSD‐positive memory relationship is influenced and altered by positive emotion dysregulation and fear of positive emotions.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, they may exhibit behavioral dyscontrol in the context of positive emotions (Weiss, Tull, Sullivan, Dixon‐Gordon, & Gratz, 2015). Indeed, empirical evidence supports that trauma‐exposed individuals, including those with PTSD severity, are nonaccepting of positive emotions, and have difficulties controlling impulsive behaviors and engaging in goal‐directed behaviors when experiencing positive emotions (Weiss, Contractor, et al, in press; Weiss, Contractor, Raudales, Greene, & Short, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Positive internal experiences, for the purposes of the current review, reference subjective experiences of positively-valenced and pleasant memories, cognitions, and emotions. Evidence indicates that trauma/PTSD severity is associated with (1) deficits in positive memory recall, access, and other processes (Contractor, Banducci, et al, 2019; Contractor, Banducci, et al, 2020; Harvey et al, 1998; McNally et al, 1995; Megías et al, 2007; Sutherland & Bryant, 2005); (2) a predominance of negative and reduced positive cognitions (Berntsen & Rubin, 2006; Foa & Kozak, 1986; Janoff-Bulman, 1992) worsened by attentional biases toward negative information/memories (Aupperle et al, 2012; Fani et al, 2012; McNally et al, 1995) and rumination on negative memories prompted by trauma reminders (Ehlers & Clark, 2000); and (3) difficulties experiencing, expressing, and/or regulating intense positive emotions (Litz et al, 2000; Weiss, Contractor, Forkus, et al, 2020; Weiss, Contractor, Raudales, et al, 2020; Weiss et al, 2018; Weiss, Nelson, et al, 2019). Indeed, disturbances in positive internal experiences are at least one of the diagnostic symptoms (D7) of PTSD’s negative alterations in cognitions and mood cluster (American Psychiatric Association, 2013).…”
mentioning
confidence: 99%
“…Further, arousal symptoms may relate to fewer cognitive resources, in turn reducing positive memory retrieval (Harvey et al, 1998). Also, research has shown that greater reckless behaviors (a PTSD arousal symptom) associate with fewer sensory details and coherence of retrieved positive memories (Banducci et al, 2020), possibly attributed to difficulties regulating positive emotions following positive memory retrieval among individuals with PTSD symptoms (Weiss et al, 2020). Lastly, hypervigilance (a PTSD arousal symptom) may involve biased attention to and appraisal of threatening stimuli and cues (Kimble & Hyatt, 2019), reducing attention to positive experiences and memories.…”
Section: Discussionmentioning
confidence: 99%